Electrochemical device

By optimizing the core structure and electrolyte composition in the electrochemical device, the lithium evolution problem caused by silicon-based materials is solved, lower expansion stress and higher ionic conductivity are achieved, and the cycle life of the battery is extended.

CN119208734APending Publication Date: 2024-12-27ZHUHAI COSMX BATTERY CO LTD

Patent Information

Application Number
CN202411345005.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-25
Publication Date
2024-12-27

AI Technical Summary

Technical Problem

During the fast charging process, the existing pure graphite battery system has excessive stress caused by the expansion of the volume of silicon-based material, which leads to lithium extraction problems, and the original structure cannot meet the needs of improving fast charging performance and energy density.

Method used

Design an electrochemical device, including a core and an electrolyte, the core consists of a positive electrode sheet, an anode sheet and a separator, the negative electrode sheet contains silicon-based materials and carbon-based materials, and the thickness relationship between the arc region and the straight region is 1.01≤X1 /H≤1.6, fluorophosphate is added to the electrolyte, and the mass content of fluorophosphate is 0.2-15 wt% to reduce the risk of lithium evolution.

Benefits of technology

By controlling the thickness relationship between the arc area and the straight area, the expansion space is reserved, the expansion stress of the active material layer is reduced, the fluorophosphate esters form a stable interface film, improve ionic conductivity and toughness, reduce lithium extraction and side reactions, and extend battery life. .

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119208734A_ABST
    Figure CN119208734A_ABST
Patent Text Reader

Abstract

The present invention relates to the field of batteries, and provides an electrochemical device, the electrochemical device comprises a roll core and an electrolyte, the roll core comprises a positive plate, a negative plate and a diaphragm, the roll core comprises a first straight region, a second straight region and an arc region connecting the first straight region and the second straight region, the negative plate comprises a negative active material layer, and the diaphragm comprises a negative active material layer. The negative active material layer comprises a silicon-based material and a carbon-based material; the roll core meets the relational expression that X1 / H is greater than or equal to 1.01 and less than or equal to 1.6; wherein X1 is the thickness of the arc area, and the unit is mm; h is the thickness of the first straight area, and the unit is mm; the electrolyte comprises fluorophosphate ester; the mass content X2 of the fluorophosphate in the electrolyte is 0.2-15, and the unit is wt%. The problem of lithium precipitation caused by overlarge stress in the circular arc area of the winding core using the silicon-based material can be obviously improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of batteries, and in particular to an electrochemical device. Background Art

[0002] In recent years, in order to improve the fast charging capability and energy density of conventional pure graphite battery systems, the compaction density of positive and negative active materials has been continuously improved. The stress on the arc of the wound cell is relatively large. Since the specific capacity of graphite is relatively low, silicon materials have a higher specific capacity, which can further improve the fast charging performance and energy density. Graphite doped with silicon has become a trend, but the volume expansion of silicon after lithium insertion is much greater than that of graphite, up to 400%. After being applied to the wound battery system, the arc is subjected to greater stress and the risk of blockage of the ion transmission channel is greater, which makes it easier to precipitate lithium during fast charging. The original arc area structure setting of the pure graphite system no longer meets the demand. Summary of the invention

[0003] The purpose of the present invention is to overcome the above-mentioned problems existing in the prior art and to provide an electrochemical device which can significantly improve the lithium deposition problem caused by excessive stress in the arc area of ​​the winding core using silicon-based materials.

[0004] In order to achieve the above-mentioned object, the present invention provides an electrochemical device, the electrochemical device comprising a winding core and an electrolyte, the winding core comprising a positive electrode sheet, a negative electrode sheet and a separator, the winding core comprising a first straight region and a second straight region, and an arc region connecting the first straight region and the second straight region, the negative electrode sheet comprising a negative electrode active material layer, and the negative electrode active material layer comprising a silicon-based material and a carbon-based material;

[0005] The winding core satisfies the relationship: 1.01≤X1 / H≤1.6;

[0006] Wherein, X1 is the thickness of the arc area, in mm; H is the thickness of the first straight area, in mm;

[0007] The electrolyte contains fluorophosphate; the mass content X2 of the fluorophosphate in the electrolyte is 0.2-15, in units of wt%.

[0008] The present invention adopts the above technical solution to achieve the following beneficial effects:

[0009] The electrochemical device of the present invention controls the thickness of the arc area and the straight area within a certain range. Under the same conditions, the thickness of the arc area is greater than the thickness of the straight area, which can reserve a larger expansion space for the arc area, so that the active material layer at the arc is at a lower low expansion stress, which can improve the arc lithium precipitation problem. However, as the cycle time continues to increase, the interface film of the positive and negative electrodes is easily affected by the expansion and extrusion of the arc area, and the rupture causes the aggravation of the side reaction between the electrolyte and the positive and negative electrode materials, resulting in the blockage of the gap between the materials and the thickening of the interface film, which causes lithium precipitation again; after adding fluorophosphate, a stable interface film can be generated at the positive electrode interface, and at the same time, it can generate a F-rich interface film at the negative electrode, and the generated interface film has high ionic conductivity and high toughness at the same time, which can improve the stress resistance and the anti-cyclic expansion and contraction of silicon-based materials, inhibit the damage of the interface film, thereby reducing side reactions, further improving the lithium precipitation problem caused by space blockage, and improving ionic conductivity.

[0010] The endpoints and any values ​​of the range disclosed in this article are not limited to the precise range or value, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of each range, the endpoint values ​​of each range and the individual point values, and the individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article. Herein, in the absence of special instructions, data ranges include endpoints. BRIEF DESCRIPTION OF THE DRAWINGS

[0011] Figure 1 Schematic diagram of a winding core in one embodiment of the present invention. DETAILED DESCRIPTION

[0012] The specific embodiments of the present invention are described in detail below. It should be understood that the specific embodiments described herein are only used to illustrate and explain the present invention, and are not used to limit the present invention.

[0013] Unless otherwise defined, all scientific and technical terms used in the present invention have the same meanings as commonly understood by one of ordinary skill in the art to which the present invention relates.

[0014] The present invention provides an electrochemical device, the electrochemical device comprising a winding core and an electrolyte, the winding core comprising a positive electrode sheet, a negative electrode sheet and a separator, the winding core comprising a first straight region and a second straight region, and an arc region connecting the first straight region and the second straight region, the negative electrode sheet comprising a negative electrode active material layer, and the negative electrode active material layer comprising a silicon-based material and a carbon-based material;

[0015] The winding core satisfies the relationship: 1.01≤X1 / H≤1.6 (its value may be, for example, 1.01, 1.05, 1.1, 1.15, 1.2, 1.25, 1.3, 1.4, 1.5, 1.6);

[0016] Wherein, X1 is the thickness of the arc area, in mm; H is the thickness of the first straight area, in mm;

[0017] The electrolyte contains fluorophosphate; the mass content X2 of the fluorophosphate in the electrolyte is 0.2-15 (its value can be, for example, 0.2, 1, 2, 4, 6, 8, 10, 12, 14, 15), in units of wt%.

[0018] In some embodiments, Figure 1 As shown, the winding core comprises a first straight area 1 and a second straight area 2, and an arc area 3 connecting the first straight area 1 and the second straight area 2. The first straight area 1 and the second straight area 2 are bounded by a horizontal (X corresponding to the direction indicated by the arrow) central axis (as shown by the dotted line), the second straight area 2 is above the central axis, the first straight area 1 is below the central axis, and the arc areas 3 on both sides connect the first straight area 1 and the second straight area 2. The thickness of the larger side of the thickness in the battery cell can be taken as the thickness of the first straight area 1.

[0019] In some embodiments, X1 is 1.2-8 (e.g., 1.2, 2, 4, 6, 8). The size of X1 can be tested by computer tomography (CT). Figure 1 The thickness of the arc regions on both sides of the battery cell may be the thickness of the arc regions measured in the width direction (X) of the battery cell.

[0020] In some embodiments, the electrochemical device further comprises a first pole lug and a second pole lug located in the first straight region, the first pole lug and the second pole lug are respectively covered with adhesive tape, and the thickness H of the first straight section is the thickness of the region between the first pole lug and the second pole lug. Due to the presence of the first pole lug, the second pole lug and the adhesive tape, the thickness of the region between the first pole lug and the second pole lug is relatively thicker than other regions, and the thickness can be the thickness of any position in the region between the first pole lug and the second pole lug.

[0021] In some embodiments, the tab glue comprises an inner rubber layer, an intermediate rubber layer and an outer rubber layer which are stacked. It should be understood that the inner rubber layer is the rubber layer close to the tab side, and the outer rubber layer is the rubber layer away from the tab side. The inner rubber layer is directly attached to the tab, and is required to have good adhesion and conductivity (or insulation, depending on the design requirements) to ensure a close connection with the tab, and may also need to withstand certain mechanical stress and chemical corrosion. The intermediate rubber layer is located between the inner rubber layer and the outer rubber layer, and plays a role in enhancing structural strength, buffering vibration and possible heat conduction. Depending on the use environment and performance requirements of the battery, the intermediate rubber layer may need to have specific physical and chemical properties. Outer rubber layer: As the outermost layer of the tab glue, its main function is to provide additional protection to prevent the external environment from eroding the internal structure, while ensuring compatibility with other battery components. The material selection and design of the outer rubber layer need to comprehensively consider multiple factors, such as temperature resistance, corrosion resistance, wear resistance, etc. The tab glue can be obtained commercially.

[0022] In some embodiments, the thickness of the tab glue is 30 μm-220 μm.

[0023] In some embodiments, H is 1.1-5 (e.g., 1.1, 1.5, 2, 2.5, 3, 3.5, 4, 4.5, 5). The size of H can be tested by computer tomography (CT). Figure 1 shown.

[0024] In some embodiments, 1.05≤H / X1≤1.25.

[0025] In some embodiments, X2 is 0.2-8 (for example, it can be 0.2, 1, 2, 3, 4, 5, 6, 7, 8).

[0026] In some embodiments, the ratio X3 of the particle size Dv50 of the carbon-based material to the particle size Dv50 of the silicon-based material is 0.2-6 (for example, it can be 0.2, 0.5, 1, 2, 3, 4, 5, 6).

[0027] In the present invention, the term "Dv50" refers to the particle size corresponding to when the cumulative volume particle size distribution percentage of a sample reaches 50%. Dv50 can be tested using a laser particle size analyzer.

[0028] In some embodiments, the content of silicon-based material in the negative electrode active material is 3-40wt%, such as 3wt%, 5wt%, 10wt%, 15wt%, 20wt%, 25wt%, 30wt%, 35wt%, or 40wt%.

[0029] In some embodiments, the powder resistivity of the negative electrode active material is 0.2 - 600 Ω·cm, such as 0.2 Ω·cm, 1 Ω·cm, 10 Ω·cm, 50 Ω·cm, 100 Ω·cm, 200 Ω·cm, 300 Ω·cm, 400 Ω·cm, 500 Ω·cm, 600 Ω·cm.

[0030] The powder resistivity can be measured by a powder resistivity meter.

[0031] In some embodiments, the carbon-based material includes at least one of artificial graphite, natural graphite, mesophase carbon microspheres, hard carbon, and soft carbon.

[0032] In some embodiments, the silicon-based material includes at least one of nano-silicon, silicon oxide material (SiO x , 0 < x < 2), and silicon-carbon material.

[0033] In some embodiments, the content of silicon element in the silicon-based material is 35 - 70 wt%, such as 35 wt%, 40 wt%, 45 wt%, 50 wt%, 55 wt%, 60 wt%, 65 wt%, 70 wt%.

[0034] In some embodiments, the particle size Dv50 of the carbon-based material is 3 μm - 20 μm, such as 3 μm, 5 μm, 8 μm, 10 μm, 12 μm, 15 μm, 18 μm, 20 μm.

[0035] In some embodiments, the particle size Dv50 of the silicon-based material is 5 μm - 15 μm, such as 5 μm, 8 μm, 10 μm, 12 μm, 15 μm.

[0036] In some embodiments, the negative electrode active material layer further includes a conductive agent and a binder.

[0037] In some embodiments, the negative electrode active material layer includes 80 - 99.8 wt% of the negative electrode active material, 0.1 - 10 wt% of the conductive agent, and 0.1 - 10 wt% of the binder.

[0038] In some embodiments, the negative electrode active material layer includes 90 - 99.6 wt% of the negative electrode active material, 0.2 - 5 wt% of the conductive agent, and 0.2 - 5 wt% of the binder.

[0039] In one embodiment, the conductive agent includes at least one of conductive carbon black, acetylene black, Ketjen black, conductive graphite, conductive carbon fiber, carbon nanotube, metal powder, and carbon fiber.

[0040] In one embodiment, the binder includes at least one of sodium carboxymethyl cellulose, styrene-butadiene latex, polytetrafluoroethylene, and polyethylene oxide.

[0041] The negative electrode current collector may be a negative electrode current collector commonly used in the art, such as copper foil or a composite current collector.

[0042] In some embodiments, the fluorophosphate comprises a compound represented by formula (I),

[0043]

[0044] Wherein, R1, R2 and R3 are each independently a substituted or unsubstituted C1-C6 alkyl group, a substituted or unsubstituted C2-C6 unsaturated aliphatic group or a substituted or unsubstituted C6-C10 aromatic group, and A contains O or S; if substituted, the substituent is a halogen (such as F, Cl, Br), and at least one hydrogen atom in the compound is replaced by a fluorine atom.

[0045] In some embodiments, R1, R2 and R3 are each independently a substituted or unsubstituted C1-C3 alkyl group (such as methyl, ethyl, propyl), a substituted or unsubstituted C2-C3 unsaturated aliphatic group (such as vinyl, propenyl, ethynyl, propynyl), or a substituted or unsubstituted C6-C8 aromatic group (such as phenyl, tolyl, ethylphenyl, xylyl, and the xylyl group may be p-xylyl, m-xylyl, or o-xylyl).

[0046] In some embodiments, the fluorophosphate contains at least one of the compounds represented by formula (I)-1 to formula (I)-5,

[0047]

[0048] In some embodiments, the electrolyte further comprises an organic solvent, a lithium salt and a functional additive.

[0049] In some embodiments, the organic solvent comprises carbonate and / or carboxylate.

[0050] In some embodiments, the carbonate comprises one or more of the following solvents: ethylene carbonate, propylene carbonate, dimethyl carbonate, diethyl carbonate, and ethyl methyl carbonate.

[0051] In some embodiments, the carboxylic acid ester comprises one or more of the following solvents: propyl acetate, n-butyl acetate, isobutyl acetate, n-amyl acetate, isoamyl acetate, ethyl propionate, n-propyl propionate, methyl butyrate, ethyl butyrate, and ethyl n-butyrate.

[0052] In some embodiments, the lithium salt comprises at least one of lithium hexafluorophosphate (LiPF6), lithium difluorophosphate (LiPO2F2), lithium difluorooxalatoborate (LiDFOB), lithium bis(trifluoromethylsulfonyl imide), lithium difluorobis(oxalatophosphate), lithium tetrafluoroborate, lithium bis(oxalatoborate), lithium hexafluoroantimonate, lithium hexafluoroarsenate, lithium bis(trifluoromethylsulfonyl)imide, lithium bis(pentafluoroethylsulfonyl)imide, tris(trifluoromethylsulfonyl)methyllithium, and lithium bis(trifluoromethylsulfonyl)imide.

[0053] In some embodiments, the functional additive comprises one or more of vinylene carbonate, vinyl carbonate, fluoroethylene carbonate (FEC), vinyl sulfate, succinonitrile (SN), glutaronitrile, adiponitrile (ADN), pimelonitrile, suberonitrile, 1,3,6-hexanetrinitrile, glycerol trinitrile, 1,2-bis(2-cyanoethoxy)ethane, 1,3-propanesultone, and propenyl-1,3-sultone (PS).

[0054] In some embodiments, the lithium salt accounts for 10wt%-25wt% of the total mass of the electrolyte, for example, it can be 10wt%, 11wt%, 12wt%, 13wt%, 14wt%, 15wt%, 16wt%, 17wt%, 18wt%, 19wt%, 20wt%, 21wt%, 22wt%, 23wt%, 24wt%, or 25wt%.

[0055] In some embodiments, the organic solvent accounts for 50wt%-80wt% of the total mass of the electrolyte, for example, 50wt%, 55wt%, 60wt%, 65wt%, 70wt%, 75wt%, or 80wt%.

[0056] In some embodiments, the added amount of the functional additive is 8wt%-25wt% of the total mass of the electrolyte, for example, it can be 8wt%, 9wt%, 10wt%, 11wt%, 12wt%, 13wt%, 14wt%, 15wt%, 16wt%, 17wt%, 18wt%, 19wt%, 20wt%, 21wt%, 22wt%, 23wt%, 24wt%, 25wt%.

[0057] In some embodiments, the positive electrode sheet comprises a positive electrode current collector and a positive electrode active material layer located on at least one side of the positive electrode current collector, the positive electrode active material layer comprises a positive electrode active material, and the positive electrode active material comprises a layered lithium composite oxide.

[0058] In some embodiments, the chemical formula of the lithium composite oxide is Li (1+x) Ni y Co z M (1-y-z)O2; where -0.1≤x≤1 (e.g. -0.1, 0, 0.1, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, 0.9, 1), 0≤y≤1 (e.g. 0, 0.1, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, 0.9, 1), 0.1≤z≤1 (e.g. 0.1, 0.2, 0.3 , 0.4, 0.5, 0.6, 0.7, 0.8, 0.9, 1), and 0.1≤y+z≤1 (for example, 0.1, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, 0.9, 1); wherein M is at least one of Mg, Zn, Ga, Ba, Al, Fe, Cr, Sn, V, Mn, Sc, Ti, Nb, Mo and Zr.

[0059] In some embodiments, the positive electrode active material includes secondary particles and primary particles.

[0060] In some embodiments, the ratio X4 of the particle size Dv50 of the secondary particles in the positive electrode active material to the particle size Dv50 of the primary particles is 2-12, such as 2, 4, 6, 8, 10, 12. By controlling the particle size ratio of the primary particles and the secondary particles of the positive electrode material, more pore space can be provided, and a better infiltration effect is provided for the fluorophosphate additive electrolyte, so that the fluorophosphate can form a stable interface film at the positive electrode, inhibit the positive electrode transition metal solvent, reduce the side reaction of the transition metal free to the negative electrode to the negative electrode active material, reduce the excessive expansion of the negative electrode caused by the side reaction, and inhibit the growth of the impedance of the cycle process, further improve the arc lithium precipitation while improving the safety and cycle performance.

[0061] In some embodiments, the particle size Dv50 of the secondary particles in the positive electrode active material is 6μm-20μm, for example, 6μm, 7μm, 8μm, 9μm, 10μm, 11μm, 12μm, 13μm, 14μm, 15μm, 16μm, 17μm, 18μm, 19μm, and 20μm.

[0062] In some embodiments, the particle size Dv50 of the primary particles in the positive electrode active material is 1 μm-8 μm, such as 1 μm, 2 μm, 3 μm, 4 μm, 5 μm, 6 μm, 7 μm, and 8 μm.

[0063] In some embodiments, the mass ratio of secondary particles to primary particles in the positive electrode active material is 0.5-2, such as 0.5, 0.8, 1, 1.2, 1.5, 1.8, and 2.

[0064] In some embodiments, the positive electrode active material layer further comprises a conductive agent and a binder. The types of the conductive agent and the binder can refer to the types of the conductive agent and the binder in the negative electrode sheet.

[0065] In some embodiments, the mass percentage of each component in the positive electrode active material layer is: 80-99.8wt% of positive electrode active material, 0.1-10wt% of conductive agent, and 0.1-10wt% of binder.

[0066] In some embodiments, the mass percentage of each component in the positive electrode active material layer is: 90-99.6wt% of positive electrode active material, 0.2-5wt% of conductive agent, and 0.2-5wt% of binder.

[0067] In some embodiments, the positive electrode current collector may be a positive electrode current collector conventionally used in the art, such as aluminum foil or a composite current collector.

[0068] In some embodiments, the electrochemical device satisfies 0.3≤X5 / X2≤4; wherein X5 is the elongation of the positive electrode current collector. The elongation of the positive electrode current collector in this range can effectively suppress the expansion of the negative electrode and avoid the breakage of the current collector caused by the expansion of the negative electrode. Too low elongation causes the current collector to break easily, and too high elongation has a low binding capacity for the negative electrode, both of which affect the performance of the battery. Fluorophosphates can generate a stable aluminum fluoride-rich protective film on the surface of the foil, improving the stability of the foil. By limiting the elongation of the current collector and the content of fluorophosphates, the risk of current collector breakage can be reduced, further reducing the risk of core deformation while improving arc lithium precipitation performance.

[0069] In the present invention, elongation refers to the percentage of the length of the tensile fractured current collector to the original length. The elongation test method is: the current collector is cut into rectangular splines with a width of 1.5 cm and a length greater than 5 cm. The extension direction of the long side of the spline is consistent with the length direction of the current collector, so that the edge of the spline is smooth and has no gaps (to prevent defects from affecting the test results). The above spline is clamped between the upper and lower clamps of the universal tensile machine, the long axis of the spline coincides with the center line of the clamp, the distance between the upper and lower clamps of the tensile machine is the specified distance of the current collector, and the specified distance in the length direction of the current collector is 5 cm. At a tensile test speed of 10 mm / min, the spline is stretched along the length direction of the spline until the current collector breaks, the size in the length direction of the current collector is obtained, and the elongation in the length direction of the current collector is calculated.

[0070] In some embodiments, X5 is 1.005-1.1, for example, 1.005, 1.01, 1.02, 1.03, 1.04, 1.05, 1.06, 1.07, 1.08, 1.09, or 1.1.

[0071] In some embodiments, the porosity of the diaphragm is 30-60%, such as 30%, 35%, 40%, 45%, 50%, 55%, and 60%. Further limiting the porosity of the diaphragm can reduce the risk of lithium deposition in the arc region due to the difficulty of lithium ion transfer caused by the diaphragm blocking caused by the expansion of the arc region. At the same time, high porosity can ensure the lithium ion transmission of the interface layer in the late cycle, improve the arc lithium deposition performance and ensure long cycle performance.

[0072] The diaphragm can be obtained commercially, and its size and material can be selected conventionally in the art. In some embodiments, the material of the diaphragm is polyolefin, such as polyethylene and / or polypropylene. In some embodiments, the thickness of the diaphragm is 6 μm-12 μm, such as 6 μm, 8 μm, 10 μm, and 12 μm.

[0073] In some embodiments, the electrochemical device is a lithium-ion battery.

[0074] In some embodiments, the electrochemical device may further include a shell that wraps the battery cell, and the shell may be made of, for example, an aluminum-plastic film.

[0075] If not otherwise specified, other options for the electrochemical device are conventional options in the art. The electrochemical device can be assembled in a conventional manner in the art.

[0076] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0077] Unless otherwise specified, the materials and reagents used in the following examples can be obtained from commercial sources.

[0078] The present invention is described in detail below in conjunction with specific embodiments, which are used to understand but not to limit the present invention.

[0079] Example 1

[0080] (1) Preparation of positive electrode

[0081] Lithium cobalt oxide, PVDF, conductive carbon black and carbon nanotubes are put into a vacuum mixer at a mass ratio of 96:2:1.5:0.5, N-methylpyrrolidone (NMP) is added, and the mixture is fully mixed under the action of the vacuum mixer until a uniform and fluid positive electrode slurry (solid content is 55wt%) is formed; the positive electrode slurry is evenly coated on an aluminum foil, dried and rolled. Among them, the particle sizes Dv50 of the secondary particles and the primary particles in the positive electrode active material are 15μm and 3μm respectively, that is, the particle size ratio X4 of the secondary particles and the primary particles in the positive electrode active material is 5, and the mass ratio is 1. The elongation X5 of the positive electrode current collector aluminum foil is 1.05.

[0082] (2) Preparation of negative electrode

[0083] The negative electrode active material (a combination of artificial graphite and silicon carbon, wherein the content of silicon carbon in the negative electrode active material is 15wt%, and the content of silicon element in the silicon carbon material is 30wt%), styrene-butadiene rubber, sodium carboxymethyl cellulose and conductive carbon black are put into a vacuum mixer at a mass ratio of 96.5:1:1:1.5, deionized water is added, and the mixture is fully mixed under the action of the vacuum mixer to finally form a uniform and fluid negative electrode slurry (solid content is 45wt%), and the above negative electrode slurry is evenly coated on a copper foil, dried, rolled, and die-cut (to obtain a negative electrode tab) to obtain a negative electrode sheet. The particle size Dv50 of graphite and the particle size Dv50 of silicon carbon are 10μm and 10μm, respectively, and the ratio X3 between the two is 1. The powder resistivity of the negative electrode active material is 100Ω·cm.

[0084] (3) Preparation of electrolyte

[0085] Prepare the electrolyte according to the following formula:

[0086] Organic solvent: 10 parts by weight of EC, 15 parts by weight of PC, 55 parts by weight of PP, and 20 parts by weight of EP;

[0087] Functional additives: 15 parts by weight of FEC, 2 parts by weight of PS, 2 parts by weight of 1,3,6-hexanetrinitrile, 2 parts by weight of ADN, and 1 part by weight of SN;

[0088] Lithium salt: 14.38 parts by weight of lithium hexafluorophosphate (LiPF6).

[0089] The electrolyte also contains X2 wt% of a fluorophosphate represented by formula (I)-1, where X2=2.

[0090] (4) Preparation of lithium-ion batteries

[0091] The diaphragm is a polyethylene diaphragm (provided by Asahi Kasei Corporation) with a thickness of 8 μm and a porosity of 40%.

[0092] The positive electrode sheet, separator and negative electrode sheet prepared above are stacked in order, ensuring that the separator is between the positive and negative electrode sheets to play an isolating role, and the positive and negative electrode ears are affixed with ear glue, and then the bare battery cell without liquid injection is obtained by winding; the bare battery cell is placed in the outer packaging foil, and the prepared electrolyte is injected into the dried bare battery cell, and the required lithium-ion battery is obtained after vacuum packaging, standing, formation, shaping, sorting and other processes.

[0093] like Figure 1 As shown, the winding core includes a first straight area 1 (with a positive electrode ear and a negative electrode ear), an arc area 3 connecting the first straight area 1 and the second straight area 2, the first straight area 1 and the second straight area 2 are bounded by a horizontal (X corresponds to the direction indicated by the arrow) central axis (as shown by the dotted line), the second straight area 2 is above the central axis, and the first straight area 1 is below the central axis, and the positive electrode ear and the negative electrode ear are covered with adhesive tape respectively. Among them, X1 is the thickness of the arc area 3, in mm; H is the thickness of the first straight area 1 (measured by the thickness of the area between the first electrode ear and the second electrode ear), in mm.

[0094] X2 is the mass content of fluorophosphate in the electrolyte, in wt%; X3 is the ratio of the particle size Dv50 of the carbon-based material to the particle size Dv50 of the silicon-based material; X4 is the particle size ratio of the positive electrode active material; X5 is the elongation of the positive electrode current collector, and the specific data of H, X1 to X5, X1 / H, and X5 / X2 are shown in Table 1.

[0095] Comparative Example 1

[0096] The operation was carried out in accordance with the method described in Example 1, except that no fluorophosphate was added to the electrolyte.

[0097] Example 2 and Comparative Example 2

[0098] The operation was carried out according to the method described in Example 1, except that H and / or X1 were different, and the specific values ​​were shown in Table 1.

[0099] Example 3 and Comparative Example 3

[0100] The operation was performed according to the method described in Example 1, except that X2 was different, and the specific values ​​were shown in Table 1.

[0101] Example 4 and Comparative Example 4

[0102] The operation is performed according to the method described in Example 1, except that X3 is different, and the specific values ​​are shown in Table 1.

[0103] Among them, when X3 is 0.5, the particle size Dv50 of the carbon-based material and the particle size Dv50 of the silicon-based material are 5 μm and 10 μm respectively, and the powder resistivity of the negative electrode active material is 80 Ω·cm;

[0104] Among them, when X3 is 5, the particle size Dv50 of the carbon-based material and the particle size Dv50 of the silicon-based material are 15 μm and 3 μm respectively, and the powder resistivity of the negative electrode active material is 250 Ω·cm;

[0105] Among them, when X3 is 0.15, the particle size Dv50 of the carbon-based material and the particle size Dv50 of the silicon-based material are 1.5 μm and 10 μm respectively, and the powder resistivity of the negative electrode active material is 50 Ω·cm.

[0106] Example 5 Group

[0107] The operation is performed according to the method described in Example 1, except that X4 is different, specifically:

[0108] Example 5-1: X4 is 3, the particle sizes Dv50 of the secondary particles and primary particles in the positive electrode active material are 9 μm and 3 μm respectively, and the mass ratio is 1.5;

[0109] Example 5-2: X4 is 9, the particle sizes Dv50 of the secondary particles and the primary particles in the positive electrode active material are 18 μm and 2 μm respectively, and the mass ratio is 0.6;

[0110] Example 5-3: X4 is 1.5, the particle sizes Dv50 of the secondary particles and primary particles in the positive electrode active material are 15 μm and 10 μm respectively, and the mass ratio is 1;

[0111] Example 5-4: X4 is 15, the particle sizes Dv50 of the secondary particles and the primary particles in the positive electrode active material are 15 μm and 1 μm respectively, and the mass ratio is 1.

[0112] Example 6 Group

[0113] The operation is performed according to the method described in Example 1, except that X5 is different, and the specific values ​​are shown in Table 1.

[0114] Table 1

[0115]

[0116]

[0117] Note: In Table 1, * indicates the same as Example 1.

[0118] Example 7

[0119] The operation was carried out according to the method described in Example 1, except that the types of fluorophosphates were different, as shown in Table 2.

[0120] Table 2

[0121] Group Fluorinated carbonate chemical formula Example 1 Formula (I)-1 Example 7-1 Formula (I)-2 Example 7-2 Formula (I)-3 Example 7-3 Formula (I)-4 Example 7-4 Formula (I)-5

[0122] Test Case

[0123] The performance of the batteries prepared in the examples and comparative examples was tested. The specific testing method is as follows. The results are shown in Table 3.

[0124] (1) Normal temperature cycle test

[0125] At 25°C, the divided battery is charged to 4.5V at 0.7C constant current and constant voltage, with a cut-off current of 0.05C, and then discharged to 3.0V at 0.5C constant current. After 800 cycles of charge and discharge, the capacity retention rate at the 800th week is calculated. The calculation formula is as follows:

[0126] Cycle capacity retention rate (%) = (800th cycle discharge capacity / first cycle discharge capacity) × 100%.

[0127] (2) Rate charging test

[0128] Place the battery in a constant temperature environment at 25℃, ① let it stand for 10 minutes, ② discharge to 3.0V with 0.2C first, ③ let it stand for 10 minutes, ④ charge to 4.45V with 0.5C rate, cut-off current 0.02C, ⑤ let it stand for 10 minutes, ⑥ discharge to 3.0V with 0.2C, ⑦ let it stand for 10 minutes. Charge to 4.45V with 3C rate, cut-off current 0.02C, collect the constant current charging ratio of 3C rate charging, constant current charging ratio = constant current charging capacity ÷ charging capacity × 100%.

[0129] (3) Lithium deposition performance evaluation

[0130] At 25°C, charge the divided battery to 4.48V at 3.0C constant current and constant voltage, cut off current 0.05C, and then discharge to 3.0V at 0.5C constant current. After 20 cycles, fully dissect the battery to confirm the lithium deposition at the interface of the arc of the battery cell. "No lithium deposition" means that no lithium deposition is observed at the arc, "mild lithium deposition at the arc" means that local non-continuous lithium branch crystals are observed at the arc, and "moderate lithium deposition at the arc" means that lithium branch crystals with a length of more than 5mm are observed at the arc.

[0131] (4) Thermal shock performance

[0132] Under 25℃ environment, discharge to 3.0V with a given current of 0.2C; leave for 5min; charge to 4.48V with a charging current of 0.2C. When the cell voltage reaches 4.48V, change to 4.48V constant voltage charging until the charging current is less than or equal to the given cut-off current of 0.05C; leave for 1h and put the cell into the oven. The oven temperature rises to 135±2℃ at a rate of 5±2℃ / min and keeps for 30min before stopping. The judgment standard is that the cell does not catch fire or explode. Record the number of passed batteries and the number of tested batteries, and express it in the form of number of passed batteries / number of tested batteries.

[0133] Table 3

[0134]

[0135]

[0136] It should be noted that, in this article, the terms "comprise", "include" or any other variants thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device. In the absence of further restrictions, an element defined by the sentence "comprises a ..." does not exclude the presence of other identical elements in the process, method, article or device including the element. In addition, it should be pointed out that the scope of the method and device in the embodiment of the present invention is not limited to performing functions in the order shown or discussed, and may also include performing functions in a substantially simultaneous manner or in reverse order according to the functions involved, for example, the described method may be performed in an order different from that described, and various steps may also be added, omitted, or combined. In addition, the features described with reference to certain examples may be combined in other examples.

[0137] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.

Claims

1. An electrochemical device, characterized in that: The electrochemical device comprises a winding core and an electrolyte, wherein the winding core comprises a positive electrode sheet, a negative electrode sheet and a separator, wherein the winding core comprises a first straight region, a second straight region, and an arc region connecting the first straight region and the second straight region, wherein the negative electrode sheet comprises a negative electrode active material layer, wherein the negative electrode active material layer comprises a silicon-based material and a carbon-based material; The winding core satisfies the relationship: 1.01≤X1 / H≤1.6; Wherein, X1 is the thickness of the arc area, in mm; H is the thickness of the first straight area, in mm; The electrolyte contains fluorophosphate; the mass content X2 of the fluorophosphate in the electrolyte is 0.2-15, in units of wt%.

2. The electrochemical device according to claim 1, characterized in that H is 1.1-5; and / or X1 is 1.2-8, and / or 1.05≤H / X1≤1.25; and / or The ratio X3 of the particle size Dv50 of the carbon-based material to the particle size Dv50 of the silicon-based material is 0.2-6.

3. The electrochemical device according to claim 1 or 2, characterized in that: The electrochemical device further comprises a first electrode tab and a second electrode tab located in the first straight region, wherein the first electrode tab and the second electrode tab are respectively covered with adhesive tape, and a thickness H of the first straight section is a thickness of a region between the first electrode tab and the second electrode tab.

4. The electrochemical device according to any one of claims 1 to 3, characterized in that: In the negative electrode active material, the content of silicon-based material is 3-40wt%; and / or The powder resistivity of the negative electrode active material is 0.2-600Ω·cm; and / or The carbon-based material comprises at least one of artificial graphite, natural graphite, mesocarbon microbeads, hard carbon and soft carbon; and / or The silicon-based material comprises at least one of nano-silicon, silicon-oxygen material and silicon-carbon material; and / or The silicon-based material contains 35-70 wt% silicon; and / or The particle size Dv50 of the carbon-based material is 3 μm-20 μm; and / or The particle size Dv50 of the silicon-based material is 5 μm-15 μm.

5. The electrochemical device according to any one of claims 1 to 4, characterized in that: The fluorophosphate contains a compound represented by formula (I), wherein R1, R2 and R3 are each independently a substituted or unsubstituted C1-C6 alkyl group, a substituted or unsubstituted C2-C6 unsaturated aliphatic group or a substituted or unsubstituted C6-C10 aromatic group, and A contains O or S; if substituted, the substituent is a halogen, and at least one hydrogen atom in the compound is replaced by a fluorine atom; Preferably, R1, R2 and R3 are each independently a substituted or unsubstituted C1-C3 alkyl group, a substituted or unsubstituted C2-C3 unsaturated aliphatic group or a substituted or unsubstituted C6-C8 aromatic group; More preferably, the fluorophosphate contains at least one of the compounds represented by formula (I)-1 to formula (I)-5, 6. The electrochemical device according to any one of claims 1 to 5, characterized in that: The positive electrode sheet comprises a positive electrode current collector and a positive electrode active material layer located on at least one side of the positive electrode current collector, wherein the positive electrode active material layer comprises a positive electrode active material, and the positive electrode active material comprises a layered lithium composite oxide; Preferably, the chemical formula of the lithium composite oxide is Li (1+x) Ni y Co z M (1-y-z) O2; Among them, -0.1≤x≤1, 0≤y≤1, 0.1≤z≤1, 0.1≤y+z≤1; Among them, M is at least one of Mg, Zn, Ga, Ba, Al, Fe, Cr, Sn, V, Mn, Sc, Ti, Nb, Mo and Zr.

7. The electrochemical device according to claim 6, characterized in that The positive electrode active material includes secondary particles and primary particles; Preferably, the ratio X4 of the particle size Dv50 of the secondary particles to the particle size Dv50 of the primary particles in the positive electrode active material is 2-12.

8. The electrochemical device according to claim 6, characterized in that The electrochemical device satisfies 0.3≤X5 / X2≤4; Wherein, X5 is the elongation of the positive electrode current collector, preferably, X5 is 1.005-1.

1.

9. The electrochemical device according to any one of claims 1 to 8, characterized in that: The porosity of the separator is 30-60%.

10. The electrochemical device according to any one of claims 1 to 9, characterized in that: The electrochemical device is a lithium ion battery.

Citation Information

Patent Citations

  • Low-temperature lithium-ion battery

    CN109888368A

  • Electrolytic solution, electrochemical device, lithium-ion secondary cell, and module

    CN110100348A

  • Battery cell of lithium ion battery, preparation method of battery cell and lithium ion battery comprising battery cell

    CN115039268A

  • Diaphragm, roll core and battery

    CN115275521A

  • Battery

    CN118589018A

Cited By

  • Lithium ion secondary battery

    CN120164900A

  • Lithium ion secondary battery

    CN120164900B